Pengaruh good corporate governance, leverage, dan ukuran perusahaan terhadap kinerja perusahaan perbankan di Indonesia - Haryanto, Ridhwan Lazuardi; Hady, Hamdy; Nalurita, Febria (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the factors that affect firm’s performance. The samples used in this study were banking companies that registered on Indonesian Stock Exchange (IDX) during period 2016 – 2021. The independent variables in this study are board meetings, audit committee, managerial ownership, institutional ownership, leverage, and firm size. The dependent variable used in this study was firm’s performance that measured by ROE. 13 banking companies used in this study were selected using purposive sampling technique. The model used in this study is random effect model. The result show that board meetings and firm size have significant effect on firm’s performance, while audit committee, managerial ownership, institutional ownership, and leverage have no effect on firm’s performance. The results of this study are expected to provide input for financial managers and investors to be more considerate of board meeting frequency and company size, because these two factors can affect the firm’s performance.